2016
DOI: 10.20937/rica.2016.32.02.04
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sugarcane Burning on Soil Carbon and Nitrogen Release Under Drought and Evapotranspiration Conditions in a Mexican Sugarcane Supply Zone

Abstract: Sugarcane cultivation is an agricultural activity of worldwide importance. This crop has been cultivated in Mexico for centuries, impacting important productive areas like the study region called Huasteca Potosina which is located at the Central-East part of Mexico. The relationship between soil conditions, weather and production per hectare allows identifying the edaphological and climatic conditions (aptitude levels) for cultivating sugarcane in the study area. The objective of this research work is to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…Te pH was more acidic, the moisture loss was about 20%, and the total nitrogen was reduced compared to not burning (Table 1). Tese results were consistent with those of Flores-Jiménez et al [36], who reported volatilized nitrogen nutrients and water loss from the soil during sugarcane burning. Arocena and Opio [37] reported that a pH decrease was generally caused by the loss of base cations during burning.…”
Section: Discussionsupporting
confidence: 91%
“…Te pH was more acidic, the moisture loss was about 20%, and the total nitrogen was reduced compared to not burning (Table 1). Tese results were consistent with those of Flores-Jiménez et al [36], who reported volatilized nitrogen nutrients and water loss from the soil during sugarcane burning. Arocena and Opio [37] reported that a pH decrease was generally caused by the loss of base cations during burning.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, studies have been carried out using 1-hydroxypyrene (1-HPO) as a biomarker to pyrene in urine samples women and children from vulnerable rural populations, indicating presence of PAHs generated from the burning of biomass for heating and cooking in the homes of these communities (Martínez-Salinas et al, 2010;Palacios-Ramírez et al, 2018). Furthermore, in research published in 2016, trans, trans-muconic acid (t, t-MA) was used as biomarker to benzene and was detected in children from rural communities in San Luis Potosí (Flores-Jiménez et al, 2016). Moreover, burning sugarcane is an important hydrocarbon source (pyrogenic) in the Huasteca Potosina (Flores-Jiménez et al, 2016), and this could be more relevant than possible hydrocarbons petrogenic sources for adjacent communities (Maioli, Knoppers, & Azevedo, 2009).…”
Section: Aliphaticmentioning
confidence: 99%
“…Furthermore, in research published in 2016, trans, trans-muconic acid (t, t-MA) was used as biomarker to benzene and was detected in children from rural communities in San Luis Potosí (Flores-Jiménez et al, 2016). Moreover, burning sugarcane is an important hydrocarbon source (pyrogenic) in the Huasteca Potosina (Flores-Jiménez et al, 2016), and this could be more relevant than possible hydrocarbons petrogenic sources for adjacent communities (Maioli, Knoppers, & Azevedo, 2009).…”
Section: Aliphaticmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomass burning can also increase if there is an increase in available hectares to plant this crop. In Mexico, this situation occurs in its main cane harvesting regions [10,11].…”
Section: Introductionmentioning
confidence: 99%